(untitled) (Mathematical Proceedings of The Widya Mandira Catholic University, 2024)
This research aims to: (1) Describe the development process and results of E-LKPD using LiveWorksheet on Quadrilateral material; (2) To describe the quality of E-LKPD using LiveWorksheet on Quadrilateral material. The method used is Research and Development (R&D) with the ADDIE development model which includes the Analysis, Design, Development, Implementation and Evaluation stages. The data presentation techniques used are observation, filling out questionnaires, and tests. The data analysis techniques used are validity analysis, practicality analysis, effectiveness analysis. The research results show that: (1) The learning media developed meets the very valid criteria with a material expert percentage score of 86.88% and a media expert percentage score of 90.7%. (2) The learning media developed meets the very practical criteria with a percentage score of 94.17%. (3) The media developed meets the effective criteria with a score of 88.89%. Thus, E-LKPD using LiveWorksheet on Quadrilateral material is categorized as valid, practical, and effective and is very suitable for use for learning mathematics